Cement Industry Value Delivery Network - A Blueprint for Networking the Flow of Material, Information and Cash - Dubey, Rameshwar; Singh, Tripti (Prabandhan: Indian Journal of Management, 2010)
Cement is a key infrastructure industry. It has been decontrolled from price and distribution on 1st March, 1989 and delicensed on 25th July, 1991. However, the performance of the industry and prices of cement are monitored regularly. Today the Indian cement industry comprises of over 130 large cement plants with an installed capacity of 160.24 million tons and more than 365 mini cement plants with an estimated capacity of 11.10 million tons per annum as per CMA (Cement Manufacturers Association of India) report published on 31st March, 2006. Apart from meeting the entire domestic demand, the industry is also exporting cement and clinker to neighboring countries like Bangladesh and Nepal. The export of cement during 2001-02 and 2003-04 was 5.14 million tons and 6.92 million tons respectively. Export during April-May, 2003 was1.35million tonnes.